2008
DOI: 10.1021/nl802981q
|View full text |Cite
|
Sign up to set email alerts
|

Electrooptic Modulation in Thin Film Barium Titanate Plasmonic Interferometers

Abstract: We demonstrate control of the surface plasmon polariton wavevector in an active metal-dielectric plasmonic interferometer by utilizing electrooptic barium titanate as the dielectric layer. Arrays of subwavelength interferometers were fabricated from pairs of parallel slits milled in silver on barium titanate thin films. Plasmon-mediated transmission of incident light through the subwavelength slits is modulated by an external voltage applied across the barium titanate thin film. Transmitted light modulation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(185 citation statements)
references
References 21 publications
3
182
0
Order By: Relevance
“…Various types of compact modulators that utilize SPPs have been proposed [1,[9][10][11][12][13][14]. Both phase and absorption modulations have been exploited to achieve high speed and low footprint of a modulator along with the CMOS-compatible technology.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of compact modulators that utilize SPPs have been proposed [1,[9][10][11][12][13][14]. Both phase and absorption modulations have been exploited to achieve high speed and low footprint of a modulator along with the CMOS-compatible technology.…”
Section: Introductionmentioning
confidence: 99%
“…1 Passive plasmonic circuits have been extensively proposed and analyzed in the last decade 2,3 but active plasmonic configurations are needed to achieve nanophotonic devices with advanced functionalities. This requires systems where the plasmon properties can be rapidly modulated by an external parameter, such as temperature, 4,5 voltage, 6,7 or electromagnetic radiation. [8][9][10] The magnetic field is another interesting candidate to control SPPs, since it is able to modify their dispersion relation.…”
mentioning
confidence: 99%
“…Among the various perovskite type oxide materials, barium titanate (BTO) is a very popular and has been extensively studied because of its some unique features such as the presence of spontaneous polarization, high dielectric permittivity, high electro-optic coefficient and good compatibility with the existing conventional semiconductor technology. 6,[23][24][25] In the recent time, some of the researchers have reported the RS phenomenon, diode characteristics, and large hysteresis in the current-voltage graph in BTO or transition metal doped BTO thin films. [26][27][28][29][30] Li et al 31 and Chang et al 28 reported the BRS behavior in the multilayer BTO thin film with a very high compliance current ∼ 100 mA.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%